Studies on the correlation between molecular physical parameters and pharmacological activities of selected marine natural products - Isrina Mohamad Saleh (Terengganu: Universiti Malaysia Terengganu, 2013)
The aim of this research project is to determine the molecular physical parameters that can be used to predict the pharmacological activities of marine natural products. For this study, fifty marine natural product molecules which had been identified to have biological activities were selected to be evaluated their physical properties using quantum mechanical software package of Gaussian 09 at the theoretical level of Density Functional Theory B3LYP/6-31G(d,p).